Occupation study of a surgery service through a queues model - Ferreira, M. A. M.; Filipe, J. A. (Applied Mathematical Sciences, 2015)
A method to study and evaluate the occupation of a Hospital Surgery Service, with some specificity in its activity, is outlined in this work. Its application is exemplified with real data and it is shown that it is simple, practical and useful and allows a practical management of the service occupation.